6x+8=4(x+9)

Simple and best practice solution for 6x+8=4(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+8=4(x+9) equation:


Simplifying
6x + 8 = 4(x + 9)

Reorder the terms:
8 + 6x = 4(x + 9)

Reorder the terms:
8 + 6x = 4(9 + x)
8 + 6x = (9 * 4 + x * 4)
8 + 6x = (36 + 4x)

Solving
8 + 6x = 36 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
8 + 6x + -4x = 36 + 4x + -4x

Combine like terms: 6x + -4x = 2x
8 + 2x = 36 + 4x + -4x

Combine like terms: 4x + -4x = 0
8 + 2x = 36 + 0
8 + 2x = 36

Add '-8' to each side of the equation.
8 + -8 + 2x = 36 + -8

Combine like terms: 8 + -8 = 0
0 + 2x = 36 + -8
2x = 36 + -8

Combine like terms: 36 + -8 = 28
2x = 28

Divide each side by '2'.
x = 14

Simplifying
x = 14

See similar equations:

| 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 | | 5(4d+8)=80 | | n(17+x)=34x-r | | 14a+20= | | y-5=28 | | 16x-3=86 | | 4(7t+1)-10=t-(t+5) | | 6(y+5)=-36 | | 3x-16=86 | | (2x^7-8y^8)(4x^6+6y^2)= | | 4n-7=45 | | 28+9x=258 | | 28+9=258 | | N+13.7=-6.3 | | 7u+4=4-7u |

Equations solver categories